1987
DOI: 10.3181/00379727-184-42487
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Dependent Elimination of 5-Fluoro-2'-deoxyuridine in the Monkey

Abstract: The kinetics of 5-fluoro-2'deoxyuridine (FdUrd) and 5-flUOrO~d (FUra) disposition after bolus intravenous injection were determined in anesthetized rhesus and cynomolgus monkeys. FdUrd disappearance from plasma was an apparent triexponential process with average half-lives of 0.5, 2, and 8 min; FUra disappearance was biphasic with average half-lives of 2 and 13 min. After FdUrd injection, FUra reached peak plasma concentrations of 15-30% of the initial FdUrd concentrations within 3 min, and then disappeared mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…In agreement with previous reports, we found that FUdR is rapidly cleared from the blood after bolus injection [1,18]. DSPC/DPPG/CHOL-Iiposomes (MLV) significantly retarded the clearance of the drug.…”
Section: Discussionsupporting
confidence: 93%